Molecular basis for the electric field modulation of cytochrome c structure and function - de Biase, Pablo Martin (2009)
Cytochrome c (Cyt) is a small soluble heme protein with a hexacoordinated heme and functions as an electron shuttle in the mitochondria and in early events of apoptosis when released to the cytoplasm. Using molecular dynamics simulations, we show here that biologically relevant electric fields induce an increased mobility and structural distortion of key protein segments that leads to the detachment of the sixth axial ligand Met80 from the heme iron. This electric-field-induced conformational transition is energetically and entropically driven and leads to a pentacoordinated high spin heme that is characterized by a drastically lowered reduction potential as well as by an increased peroxidase activity. The simulations provide a detailed atomistic picture of the structural effects of the electric field on the structure of Cyt, which allows a sound interpretation of recent experimental results. The observed conformational change may modulate the electron transfer reactions of Cyt in the mitochondria and, furthermore, may constitute a switch from the redox function in the respiratory chain to the peroxidase function in the early events of apoptosis.